Lentil flour: nutritional and technological properties, in vitro digestibility and perspectives for use in the food industry. (August 2021) - Romano, Annalisa; Gallo, Veronica; Ferranti, Pasquale; Masi, Paolo
Graphical abstract: Highlights: An overview of lentil flour as novel ingredient in food technology is provided. Lentil flour may improve nutritional quality, acceptance and health properties. Treatment of antinutritionals and allergens of lentil flour is discussed. Lentil flour improves the sensory and technological properties of fortified yogurt. Lentil flour can be used for decreasing the lipid content and glucose release. Abstract : The use of lentil flour in bakery (bread, cake, crackers), extruded (pasta, snacks) and other products (dressings, soups, dairy and meat products) is gaining attention of food technologists and of industry as well as popularity among consumers due to an excellent and balanced nutritional composition. This research interest has extended our knowledge of nutritional and functional properties (solubility, emulsification, gelation, foaming) of lentil flour, which, in turn, has disclosed its technological potential for preparation of high-quality foods (gluten free bakery, yogurt and meat products). However, addition of lentil flour may introduce technological problems and novel allergens. This review covers the use of lentil flour in food preparations, with focus on protein and starch digestibility and on the challenges to design lentil-based products with improved quality.